Lysosomal perturbations in human dopaminergic neurons derived from induced pluripotent stem cells with PARK2 mutation - Okarmus, J; Bogetofte, H; Schmidt, SI; Ryding, M; García-López, S; Ryan, BJ; Martínez-Serrano, A; Hyttel, P; Meyer, M (Springer Nature, 2020)
Mutations in the PARK2 gene encoding parkin, an E3 ubiquitin ligase, are associated with autosomal recessive early-onset Parkinson’s disease (PD). While parkin has been implicated in the regulation of mitophagy and proteasomal degradation, the precise mechanism leading to neurodegeneration in both sporadic and familial PD upon parkin loss-of-function remains unknown. Cultures of isogenic induced pluripotent stem cell (iPSC) lines with and without PARK2 knockout (KO) enable mechanistic studies of the effect of parkin deficiency in human dopaminergic neurons. We used such cells to investigate the impact of PARK2 KO on the lysosomal compartment and found a clear link between parkin deficiency and lysosomal alterations. PARK2 KO neurons exhibited a perturbed lysosomal morphology with enlarged electron-lucent lysosomes and an increased lysosomal content, which was exacerbated by mitochondrial stress and could be ameliorated by antioxidant treatment. We also found decreased lysosomal enzyme activity and autophagic perturbations, suggesting an impairment of the autophagy-lysosomal pathway in parkin-deficient cells. Interestingly, activity of the GBA-encoded enzyme, β-glucocerebrosidase, was increased, suggesting the existence of a compensatory mechanism. In conclusion, our data provide a unique characterization of the morphology, content, and function of lysosomes in PARK2 KO neurons and reveal an important new connection between mitochondrial dysfunction and lysosomal dysregulation in PD pathogenesis.